REFLECTION REGARD GENDER BEYOND THE PHYSICAL EDUCATION AT THE CONTEMPORARY SCHOOL ENVIRONMENT (Fiep Bulletin - online, 2020)
The present study presents the discussion about gender in the school regarding the person with and without disability. The methodology used shows some strategies of teaching and discussion about the subject through literature review in a reflexive way. In conclusion, it is observed that the contemporary school cannot be based on the pedagogical structures of the last century and needs to be reinvented. Understanding the cultural moment, the transformations of realities, the acceptance of the other, the social inclusion and above all, to tie technology and social media is an urgent need for physical education classes regarding gender at the contemporary school.